Interkoneksi Antara Parameter Pendidikan Profesional Guru dengan Hasil Belajar Siswa di Indonesia - Purwanto, Wawan; Hidayat, Nuzul; Saputra, Hendra Dani; Arif, Ahmad; Saputra, Riko (Universitas Negeri Padang, 2025)
Effective education is crucial for instructing students to attain competencies aligned with the curriculum of their educational level. This study aims to assess the teaching profession and its correlation with teacher performance, professionalism, and teacher confidence in connection with student learning outcomes. This research was carried out on vocational educators in West Sumatra who have participated in the teacher professional education program. This research employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) analytical technique. Data was gathered through purposive sampling from vocational educators in vocational high schools in West Sumatra. The findings indicated that teacher professional education (X1) exerts a significant direct influence on Teacher Performance in the Merdeka Curriculum (Z1), Professional Teachers in Indonesia (Z2), and Self-Confidence (Z3), in addition to Student Learning Outcomes (Y1). Notably, professional teachers have a substantial impact on the execution of the Merdeka Curriculum in contemporary vocational high schools, as evidenced by the largest path coefficient of the relationship between X1 and Z1 (0.558). Professional education for vocational high school teachers in West Sumatra has a significant effect on teacher professionalism, self-confidence and improving student learning outcomes, even though Indonesia is implementing a new curriculum, namely the Merdeka curriculum, teachers are still ready to be professional, confident to have an impact on student learning outcomes.